Edukasi Dan Demonstrasi: Daur Ulang Sampah Menjadi Ekoproduk sebagai Inovasi Hijau di SMK Negeri 1 Tembilahan - Mukiyat, Chairul; Damanik, Aditia Robintang; Nugroho, Prasetyo Agung; Ermizon, Rehan; Zahrani, Cindy Aulya; Alifah, Fathinah; Adisti, Salsabilla Apriyolla; Hanun, Ummu; Khaira, Dian Rahmawati; Azrul, Azrul; Prawara, Fiqih Vito; Yuska, M. Thoriqul Khairi; Ghozi, Muhammad Fikri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The waste problem in Tembilahan City remains a prominent environmental issue, marked by piles of organic and inorganic waste that have not been optimally handled. To address this, educational activities and demonstrations of recycling waste into eco-products were conducted at SMK Negeri 1 Tembilahan. The aim of this activity was to improve students' understanding and skills in sustainable waste management. The method used was a descriptive qualitative approach through observation, interviews, documentation, and pre-test and post-test evaluations of 59 students. The pre-test results showed an average score of 82 with a range of 30–90, indicating uneven initial understanding. After the activity, the post-test showed a significant increase with an average score of 96.78 and a range of 70–100. This activity also included hands-on practice in making pots from used bottles and liquid organic fertilizer (POC). Students' enthusiasm was high, reflected in their active participation throughout the activity. This education has proven effective in increasing environmental literacy and encouraging creative and sustainable waste management habits.